Molecular Aging of Human Liver: An Epigenetic/Transcriptomic Signature. (15th March 2018) - Bacalini, Maria Giulia; Franceschi, Claudio; Gentilini, Davide; Ravaioli, Francesco; Zhou, Xiaoyuan; Remondini, Daniel; Pirazzini, Chiara; Giuliani, Cristina; Marasco, Elena; Gensous, Noémie; Di Blasio, Anna Maria; Ellis, Ewa; et al.
Abstract: The feasibility of liver transplantation from old healthy donors suggests that this organ is able to preserve its functionality during aging. To explore the biological basis of this phenomenon, we characterized the epigenetic profile of liver biopsies collected from 45 healthy liver donors ranging from 13 to 90 years old using the Infinium HumanMethylation450 BeadChip. The analysis indicates that a large remodeling in DNA methylation patterns occurs, with 8, 823 age-associated differentially methylated CpG probes. Notably, these age-associated changes tended to level off after the age of 60, as confirmed by Horvath's clock. Using stringent selection criteria, we further identified a DNA methylation signature of aging liver including 75 genomic regions. We demonstrated that this signature is specific for liver compared to other tissues and that it is able to detect biological age-acceleration effects associated with obesity. Finally, we combined DNA methylation measurements with available expression data. Although the intersection between the two omic characterizations was low, both approaches suggested a previously unappreciated role of epithelial–mesenchymal transition and Wnt-signaling pathways in the aging of human liver.